TINJAUAN KONSEP ARSITEKTUR REGIONALISME SEBAGAI BAHAN PERTIMBANGAN PADA PENERAPAN FASILITAS PERTUNJUKAN KESENIAN LOKAL - Annisa, Agista Renata; Hastijanti, Retno; Murti, Farida (Jurnal Teknik Gradien, 2024)
Distinctive features in architecture need to be preserved because it is part of the ancestral cultural heritage which is now one of the privileges and richness of local culture. Along with the times and technological advances, it causes a new and different mindset such as the existence of modern art, so that local people become less interested in local art, especially in Salatiga City. In addition to the lack of interest in local arts, there is also a lack of performance facilities for local arts that are useful as a place to accommodate performances and are supported by exhibitions and training which is one way to preserve Salatiga's local art. With the design of local art performance facilities that will accommodate local art activities with performances supported by exhibitions and training, it is expected to foster interest and talent as one of the efforts to preserve Salatiga's local art. The design of performing arts facilities that will use regionalism architecture will continue to apply in terms of local architecture and local culture of the Salatiga area as one of the design elements. With qualitative descriptive methods, the author will analyze the basic theories as well as architectural concepts of regionalism.